TeknÃ¡âa vanishing oral tradition among the Kayan people of Sarawak, Malaysian Borneo - Wan, R. (Routledge, 2018)
The documentation of the oral traditions of non-literate indigenous communities is a vital aspect of the preservation and survival of indigenous knowledge, culture and tradition. In this article, we discuss tekná, an oral tradition of the Kayan people in Sarawak. Here we trace not only the historical background of tekná, but also explore its current status and practices among the Kayan. We present an example of tekná sung by a Kayan elder. This forms the basis for a discussion about how the tekná is performed, sung, and narrated, as well as the possible meanings and interpretations that can be gleaned from this tekná. Finally, we suggest approaches to documenting oral traditions like tekná that show promise for the preservation of this fragile oral tradition for future generations of Kayan. © 2018, © 2018 Editors, Indonesia and the Malay World.